Effects of Dietary Curcumin on Growth and Digestive Physiology of Seriola dumerili - Yang, Jingru; Hong, Jiawei; Fu, Zhengyi; Ma, Zhenhua (Frontiers in Marine Science, 2022)
In order to understand the effects of dietary curcumin on the growth and digestive performance of Seriola dumerili, this study was conducted under laboratory condition. The control group was added with 0% curcumin, and two treatment groups were added with 0.01% and 0.02% curcumin, respectively. Fish were fed with experimental diet for eight weeks. The growth data, crude muscle composition, growth genes, intestinal digestive enzymes and tissue parameters, blood lipid related indicators were measured, and the correlation between digestive indicators, growth gene indicators and growth characteristics indicators was analyzed. The results showed that the survival rate, visceral ratio, Hepatosomatic ratio and condition factor of Seriola dumerili increased first and then decreased with the increase of curcumin content in feed. The feed conversion ratio of the control group was significantly higher than that of the treatment group. With the increase of curcumin content in feed, lipase and trypsin increased first and then decreased with the increase of curcumin content. Compared with the control group, curcumin significantly increased the muscle thickness and the number of goblet cells of Seriola dumerili. The crude fat content of muscle first increased and then decreased with the increase of curcumin content, reaching the minimum value in the control group. Muscle water content was just the opposite. High and low content of curcumin can reduce the content of serum total cholesterol and triglyceride, and low dose (0.01%) of curcumin has the strongest lipid-lowering effect. The relative gene expression of IGF1 and IGF2 reached the maximum in 0.02% treatment group. The results showed that the addition of curcumin in feed could improve the survival rate, feed efficiency and other growth characteristics of Seriola dumerili, improve intestinal digestion and structure, promote intestinal health, reduce blood lipids, and increase the nutritional value, taste and flavor of Seriola dumerili. The best effect was achieved in the 0.01% treatment group. The results of this study provide a theoretical reference for the feasibility of adding curcumin to Seriola dumerili feed in production, and realize the optimal proportion of feed additives for this species, which is beneficial to the sustainable development of aquaculture.